Assessment of Implementation of Antimicrobial Resistance Surveillance and Antimicrobial Stewardship Programs in Tanzanian Health Facilities a Year After Launch of the National Action Plan - Sangeda, Raphael Z.; Kibona, Joel; Munishi, Castory; Arabi, Frank; Manyanga, Vicky P.; Mwambete, Kennedy D.; Horumpende, Pius G. (Frontiers in Public Health, 2020)
Introduction: Antimicrobial resistance (AMR) is a current global health threat and a challenge to the treatment of infectious diseases. The WHO advocates a strategy of antibiotic stewardship programs (ASP) in optimizing antimicrobial use in hospitals. This study aimed at assessing the existence of AMR surveillance and ASP implementation in health facilities in Tanzania in the year following the launch of the National Action Plan (NAP). Methodology: From December 2017 through July 2018, a descriptive cross-sectional study was conducted using a structured questionnaire administered online. A total of 199 health facilities in Tanzania mainland whose contacts was obtained from the Ministry of Health Community Development Gender Elderly and Children (MoHCDGEC) were reached by phone and thereafter, a survey was sent via text or e-mail to focal persons in the corresponding facilities. Results: Only 39 (32.5%) responses from contacted facilities were received and analyzed. Thirty (76.9%) of the facilities were government-owned. Of the 39 respondents surveyed, 13 (35.9%) declared to have implemented some sort of coordinated ASP to promote the rational use of antimicrobials at their facilities. The respondents reported the presence of guidelines for the implementation of ASP at variable proportions, whereas the presence of a committee for Infection Prevention and Control was reported by 27 (69.2%). Twenty-four (61.5%) had a Medical and Therapeutic Committee. Although all 39 (100%) respondents were aware of the presence of AMR in Tanzania, only 26 (66.7%) were aware of the presence of the Tanzanian NAP for AMR. Hospital antibiotic policy document was present in 6 (15.4%) facilities. Only 7 (17.9%) facilities conducted prescription auditing; 9 (23.1%) had a hospital formulary; 14 (35.9%) had standard hospital prescription. 9 (23.1%) had software for data storage about AMR. Only 7 (17.9%) facilities conducted microorganisms' susceptibility tests and kept the record of the microorganism susceptibility testing. Conclusion: Our study found the existence of AMR surveillance activities and ASP implementation in Tanzania, albeit at a low level. The implementation was inconsistent across the surveyed facilities. These data have identified areas of improvement in addressing AMR in Tanzania through the NAP.